1986
DOI: 10.1007/bf00966121
|View full text |Cite
|
Sign up to set email alerts
|

Myelin lipids: A phylogenetic study

Abstract: The lipid composition of CNS and PNS myelin was studied in rat, Xenopus, trout and Torpedo. The main difference lay in the proportion of cerebrosides, which decreased in the sequence rat greater than Xenopus greater than Torpedo greater than trout. In addition Torpedo CNS and PNS myelins were extremely rich in sulfatides. In some respects, Torpedo appeared closer to tetrapods than trout. Otherwise the proportion of the different lipid classes did not reveal any clear evolutionary trends. The presence of hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 29 publications
1
8
0
2
Order By: Relevance
“…A similar lipid composition has been reported for other teleosts, and the same lipids are present in higher vertebrates [16]. Phosphatidylcholine was more abundant in the PNS than CNS, in contrast to that of trout that had displayed similar levels [16,48], and ran ahead of the standard.…”
Section: P0-like Proteins Were Found In Both the Cns And Pns Myelins supporting
confidence: 74%
“…A similar lipid composition has been reported for other teleosts, and the same lipids are present in higher vertebrates [16]. Phosphatidylcholine was more abundant in the PNS than CNS, in contrast to that of trout that had displayed similar levels [16,48], and ran ahead of the standard.…”
Section: P0-like Proteins Were Found In Both the Cns And Pns Myelins supporting
confidence: 74%
“…Indeed, the high cholesterol level in myelin may have evolved by its molecular association with PLP. This idea is supported by the finding that the cholesterol content of myelin is similar across various tetrapod species (Burgisser et al, 1986) but lower in fish (Kirschner et al, 1989). Together this suggests an intriguing correlation between the evolutionarily increased abundance of PLP and of cholesterol in CNS myelin at the root of tetrapods, coinciding with the emergence of the PLP-specific loop.…”
Section: Coevolution Of Myelin Protein and Lipid Compositionmentioning
confidence: 70%
“…Previous studies have identified the major myelin proteins present in teleosts (Burgisser et al, 1986). To confirm that these proteins are similar in zebrafish, myelin was purified from adult zebrafish brains, using sucrose gradients, separated on a 4 -12% gradient acrylamide gel, and stained with GelCode Blue reagent (Pierce) to reveal major myelin proteins (p100, p64, p36, p24, p17, p14, and p8) (Fig.…”
Section: Protein Composition Of Zebrafish Myelin Is Similar To Mammalmentioning
confidence: 98%